(untitled) (Informatica, 2024)
This paper analyzes the basic customer management process and chooses the Apriori algorithm to build a CRM model based on data mining. In addition, this paper designs a customer relationship management system based on big data. The system is divided into three layers: data source, batch processing, and real-time processing. In the part of constructing the system architecture, this paper adopts the Hadoop platform. The batch processing layer, it has consisted of four parts, which include No SQL database, Oracle database, ETL architecture, and Hadoop platform. This paper gives the logical architecture design diagram. The real-time processing layer mainly includes a real-time decision engine and service bus. The key part of this layer is the real-time decision engine, in the design of which the Bayesian algorithm and product recommendation prediction model are used. Finally, this paper takes K company as an example to demonstrate the model and management system. After applying the analytical model and management system, the sales of K company keep increasing.